MARKETING POLITIK: ANALISIS TERHADAP KOMPETISI ELEKTORAL PADA PEMILIHAN PRESIDEN TAHUN 2024 DI INDONESIA - Toguan Rambe; Seva Maya Sari; Mawardi Mawardi (IAIN Padangsidimpuan, 2023)
The political process in Indonesia has entered into increasingly dynamic specially as the leadership transition momentum approaches in 2024, this phenomenon can be seen in electoral political marketing in several names of figures who have the potential to become candidates for the election. This paper is a descriptive analysis of the phenomenon of presidential elections. in Indonesia, the type of research used is qualitative. The method of collecting research data is observation through library research or literature review. His position is often also called a literature survey, therefore the object of this research is all written data, whether found in books, articles or research results as well as infographics both published in print and electronic media. The results of the study explain that marketing is interpreted as an ongoing political method or strategy both carried out by individuals and certain political parties in absorbing people's aspirations, facilitating contestants in voicing ideas and ideas. In principle, political marketing is part of a strategy aimed at winning contests. All instruments that are part of marketing are very urgent, including candidates, parties or combinations of political parties, winning teams, volunteers and even the media. Accumulating that these political instruments must run and process simultaneously and linearly so that the political messages, vision, mission and work programs offered to the public are well absorbed.